Strength and Stiffness of Joints in Rattan Furniture - Wan Ariffin, Wan Tarmeze (1994)
A study was conducted with the objective of gathering information on the strength and stiffness properties and behaviour of joints in rattan furniture subjected to various kinds of load. Four types of joint commonly found in rattan furniture making industry, i.e., nailed (N), nailed and bound with rattan rope (N+B), screwed (S), and screwed and bound (S+B) were tested in with drawal, lateral and bending loads. The results showed that in generals crewed joints were stronger and stiffer than nailed joints. Furthermore, although bindings have increased the joint strength, the bindings have not improved the joint stiffness against the all types of load, except the side bending load. Regression analyses showed that the rattan specific gravity has significantly influenced the withdrawal and later all strength. The results of the analyses have also provided some in sights especially on how the nails, screws or bindings were contributing to the strength and stiffness properties of the joints. Through this knowledge, theoretical models were developed for predicting the bending and side bending rotational stiffnesses of the joints. In the first model, the bending stiffness was proportional to the withdrawal stiffness of joint. The second model showed that the side bending stiffness was much determined by the bending properties (El) of the embedded fasteners. Beside its predictive functions, the thearetical models were envisaged to be a basis for future efforts to develop better rattan jointing methods.